Shamir-based virtual machine placement policy - Junfeng TIAN; Zilong WANG; Xinfeng HE; Zhen LI (Tongxin xuebao)
In order to alleviate the harm of co-location attack in cloud environment,a virtual machine placement strategy based on Shamir was proposed,and a virtual machine placement framework was designed.The security of key data was ensured by the blockchain in the proposed placement strategy.The virtual machine placement policy could effectively improve the security of the virtual machine and the load balancing capability of the cloud environment,and reduce resource waste.Finally,the effectiveness of the scheme is proved by simulation experiments.